Afecciones autoinmunes : de fenómeno a síntoma (2012)
ABSTRACT: This article proposes the hypothesis that autoimmune conditions could be understood as symptoms, which opens up a new clinical perspective on this matter. This work investigates the idea of conversive symptoms in Freud and Lacan’s notion that a symptom is an event of the body. It also presents the logics that could result in an autoimmune condition in some people: either as a purely organic phenomenal manifestation that does not concern them as subjects; as a phenomenon that becomes a symptom thanks to the introduction of a word device; or as a symptom constituted before interviews conducted during this investigation.